Meat intake and risk of colorectal polyps: results from a large population-based screening study in Germany - Carr, Prudence R.; Holleczek, Bernd; Stegmaier, Christa; Brenner, Hermann; Hoffmeister, Michael (The American journal of clinical nutrition, 2017)
Background: Red and processed meats have been shown to be associated with colorectal adenomas in many, but not all, studies, and the association according to the type of colorectal adenoma or the location in the colorectum is unclear. Objectives: We investigated the association of meat intake in relation to colorectal polyps and further investigated the association according to histologic subtypes and subsites in a large population-based screening study in Germany. Design: In this cross-sectional study, 15,950 participants aged ≥55 y underwent a screening colonoscopy. We calculated prevalence ratios (PRs) and 95% CIs for associations between meat intake and the most-advanced findings from a colonoscopy with the use of log binomial regression. Results: Overall, 3340 participants (20.4%) had nonadvanced adenomas, 1643 participants (10.0%) had advanced adenomas, and 189 participants (1.2%) had colorectal cancer. We observed no statistically significant association between red or processed meat consumption and the prevalence of any adenomas or advanced adenomas [highest compared with lowest: red meat, PR: 1.07 (95% CI: 0.83, 1.37); processed meat, PR: 1.11 (95% CI: 0.91, 1.36)]. In site-specific analyses, although no dose-response relation was observed, processed meat was positively associated with the prevalence of advanced adenomas in the rectum only (multiple times per day compared with <1 time/wk, PR: 1.87; 95% CI: 1.19, 2.95). Poultry intake was not associated with any outcome. Conclusions: On the basis of this large colonoscopy-based study, there are no significant associations between red or processed meat intake and the prevalence of any adenomas or advanced adenomas. However, processed meat may be positively associated with the prevalence of advanced adenomas in the rectum, but prospective cohort studies are needed to further clarify this association. There is no association between poultry consumption and the prevalence of colorectal polyps in this study.
Gesehen am 26.06.2017